Impact of COVID-19 on Well-Being in Child-Rearing Families: A Systematic Review of Longitudinal Studies - Qiting Lin; Takafumi Soejima; Shiqi Zhang; Mari Kitao (Social Sciences)
The coronavirus disease 2019 (COVID-19) pandemic has disrupted society, economy and family life. However, the impact of the pandemic on well-being in child-rearing families has not been fully studied, particularly regarding the changes before and during the pandemic and its long-term effects. This systematic review aimed to examine the impact of the COVID-19 pandemic on family well-being by focusing on changes before and during the COVID-19 pandemic. Our systematic review (PROSPERO protocol ID: CRD42023420175) extracted 2148 references from MEDLINE, CINAHL and PsycINFO, including 15 longitudinal studies published between January 2020 and October 2024. We examined the association between COVID-19 and the well-being of child-rearing families following the PRISMA guidelines. The level of family functioning and parent–child relationship quality generally declined during the COVID-19 pandemic compared to the pre-pandemic situation, while family chaos and conflict increased. However, some families reported improved functioning and no significant changes in family satisfaction. Overall, the impact of the pandemic on family well-being varied by region. These findings suggest that healthcare providers should continue to monitor dynamic family health and provide targeted support.